Safety and efficacy of a feed additive consisting of a dried extract from Garcinia gummi‐gutta (L.) Roxb. for use in cats and dogs (C.I.A.M.). (8th March 2021) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Durjava, Mojca Fašmon; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; Pechová, Alena; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of dried extract from Garcinia gummi‐gutta (L.) Roxb. (Garcinia extract) when used as a sensory additive in feed for cats and dogs. Garcinia extract is specified to contain at least 60% hydroxycitric acid. Since about 25% of the composition of the extract remained uncharacterised and in the absence of complete toxicological data, the FEEDAP Panel was unable to conclude on the safety for cats and dogs. In the absence of adequate data, no conclusions can be on the safety for the user. In the absence of evidence that the extract acts as a flavour in animal feed or has an effect on palatability, the FEEDAP Panel was unable to conclude on the efficacy of the additive.